The effect of direct democracy on income redistribution: evidence for Switzerland - Feld, Lars P.; Fischer, Justina A. V.; Kirchgässner, Gebhard (Economic inquiry, 2010)
In political economics, the impact of institutions on income redistribution is mainly studied by comparing different forms of representative democracy. In this article, we analyze the influence of direct democratic institutions on redistribution first focusing on welfare and nonwelfare spending using yearly panel data for Swiss cantons. Then, we estimate a model, which explains the determinants of actually achieved redistribution measured by Gini coefficients. While our results indicate that less public funds are used to redistribute income, inequality is not reduced to a lesser extent in direct than in representative democracies for a given initial income distribution. (JEL D7, D78, I30, H75, H11)